Tekstualność i teatralność - Popczyk-Szczęsna, Beata (Wydawnictwo Naukowe UAM, 2007)
The book by Patrice Pavis Le theatre contemporain. Analyse des textes, de Sarraute k Vinaver comprises the collection of essays on the contemporary French drama. The author proposes the textual analysis, which takes into account all levels of the composition of discourse. The reception of a drama is understood in terms of stage production made by a reader; because in the process of reading he both reproduces the dramatic situation (semantic aspect) and he decodes the situation of expression (stage aspect). The above mentioned mode of reading may be applied not only to drama. Two texts have been analyzed in the article: the poem Terrorysta, on patrzy (The terrorist, he is watching) by Wisława Szymborska - an example of a lyrical statement constructed in a similar way as the theatrical situation and the drama Terroryści (Terrorists) by Ireneusz Iredyński - an example of text, which is characterized by the predominance of rhetoric over theatricality. The meaning of these works results from the oscillation between the structure of text and its theatrical potential.
Textuality and theatricality